Near-Infrared Light-Triggered Bacterial Eradication Using a Nanowire Nanocomposite of Graphene Nanoribbons and Chitosan-Coated Silver Nanoparticles - Zhou, Ming; Gan, Hui-Qi; Chen, Guo-Rong; James, Tony D; Zhang, Bin; Hu, Qiang; Xu, Fugui; Hu, Xi-Le; He, Xiao-Peng; Mai, Yiyong (Frontiers in Chemistry, 2021)
Bacterial infection is a major threat to human health. However, many antibacterial agents currently used are severely limited due to drug-resistance, and the development of side effects. Herein, we have developed a non-antibiotic nanocomposite consisting of chitosan (ChS) coated silver nanoparticles (AgNPs) and graphene nanoribbon (GNR)-based nanowires for light-triggered eradication of bacteria. The presence of AgNP/ChS significantly enhanced the interactions of the GNR nanowires with Pseudomonas aeruginosa, a clinically common gram-negative bacterium. Which enables the highly effective photothermal eradication of bacteria by GNR upon near-infrared light irradiation. The nanocomposite was shown to be applicable for the light-triggered eradication of bacterial biofilms and the inhibition of bacterial growth on medical patches used for abdominal-wall hernia surgery.